Virtual Physics Laboratory with Real World Problem Based on Ngada Local Wisdom in Basic Physics Practicum - Kua, Maria Yuliana; Suparmi, Ni Wayan; Laksana, Dek Ngurah Laba (Journal of Education Technology, 2021)
This research is based on the problem where practical activities in the Basic Physics Practicum course can no longer be carried out optimally due to changes in the learning model from face-to-face (offline) to online (online) during the COVID-19 pandemic. The purpose of this study was to develop a virtual physics laboratory as a medium in carrying out practical activities and to analyze the feasibility of the product through the validation results of experts and the results of product trials on prospective users. This type of research is Research & Development with ADDIE development model. The subjects of this study were 12 lecturers and 47 students of the STKIP Citra Bakti science education study program. Data collection techniques using validation sheets and questionnaires. The data collection instruments are in the form of validation assessment sheets and response questionnaires of prospective users. The data from this study were analyzed qualitatively descriptive to decide the feasibility of the product being developed. The results of the research showed that the average validation score of the material expert was 4.63, the media expert was 4.41, the learning design expert was 4.30, and the linguist was 4.51. The validation results of the four validators are in the very good category. Meanwhile, the results of product trials to lecturers and students as potential users are in the very good category with an average score of 4.53 and 4.57, respectively. Based on these data, this virtual physics laboratory product with real world problems based on Ngada local wisdom is recommended to be applied to the Basic Physics Practicum course and to help students in their independent practicum activities.